PERBEDAAN PENGARUH PEMBERIAN WILLIAM FLEXION EXERCISE DAN ISOMETRIC EXERCISE TERHADAP PENINGKATAN KEMAMPUAN FUNGSIONAL PADA PENDERITALOW BACK PAIN NON SPESIFIK - Rafif Himawan Nimasdwi Putra; Agus Riyanto; Suci Muqodimatul Jannah (Bajang Institute, 2025)
Background: Non-specific low back pain (NSLBP) is a common musculoskeletal disorder among the elderly, leading to reduced functional ability and quality of life. William Flexion Exercise (WFE) and Isometric Exercise (IE) are two physical therapy interventions aimed at reducing pain and improving functional ability; however, the comparison of their effectiveness has not been extensively studied in the elderly population in Indonesia. Objective: This study aims to compare the effects of WFE and IE on improving functional ability in patients with LBP in the Bugar Mandiri elderly health center group in Tegalrejo, Yogyakarta. Methods: A quasi-experimental study with a pre-test and post-test design was conducted on 36 elderly individuals aged 60– 75 years, randomly divided into a WFE group (n = 18) and an IE group (n = 18). Interventions were administered three times a week for four weeks, with WFE including pelvic tilt, single knee to chest, double knee to chest, and hamstring stretch movements, and IE including curl up, side bridge, and bird dog exercises. Functional ability was measured using the Oswestry Disability Index (ODI), and pain intensity was assessed using the Visual Analogue Scale (VAS). Data analysis used the Shapiro-Wilk normality test, Levene's homogeneity test, paired t-test for effects within groups, and independent t-test for comparisons between groups. Results: Both groups showed a significant increase in functional ability (ODI) and a decrease in pain (VAS) (p<0.001). The WFE group had an ODI score of 31.5 before treatment and 26.56 after treatment, while the VAS score was 4.17 before treatment and 2.61 after treatment. Meanwhile, the IE group showed an ODI score of 28.22 before treatment and 23.33 after treatment, while the VAS score was 3.89 before treatment and 2.67 after treatment. However, the independent t-test showed no significant differences between groups in ODI (p=0.066) and VAS (p=0.879). Conclusion: WFE and IE are both effective in improving functional ability and reducing pain in patients with NPBNS, with no significant difference between the two interventions. Recommendation: Both exercises can be recommended as physiotherapy interventions for NPBNS in the elderly, taking into account patient comfort and clinical needs. Further research with larger samples and longer intervention durations is needed to confirm these findings.